Disorder-specific and shared neurophysiological impairments of attention and inhibition in women with attention-deficit/hyperactivity disorder and women with bipolar disorder. Issue 3 (10th November 2015) - Michelini, G.; Kitsune, G. L.; Hosang, G. M.; Asherson, P.; McLoughlin, G.; Kuntsi, J.
Abstract : Background: In adults, attention-deficit/hyperactivity disorder (ADHD) and bipolar disorder (BD) have certain overlapping symptoms, which can lead to uncertainty regarding the boundaries of the two disorders. Despite evidence of cognitive impairments in both disorders separately, such as in attentional and inhibitory processes, data on direct comparisons across ADHD and BD on cognitive–neurophysiological measures are as yet limited. Method: We directly compared cognitive performance and event-related potential measures from a cued continuous performance test in 20 women with ADHD, 20 women with BD (currently euthymic) and 20 control women. Results: The NoGo-N2 was attenuated in women with BD, reflecting reduced conflict monitoring, compared with women with ADHD and controls (both p < 0.05). Both ADHD and BD groups showed a reduced NoGo-P3, reflecting inhibitory control, compared with controls (both p < 0.05). In addition, the contingent negative variation was significantly reduced in the ADHD group ( p = 0.05), with a trend in the BD group ( p = 0.07), compared with controls. Conclusions: These findings indicate potential disorder-specific (conflict monitoring) and overlapping (inhibitory control, and potentially response preparation) neurophysiological impairments in women with ADHD and women with BD. The identified neurophysiological parameters further our understanding of neurophysiological impairments in women with ADHD and BD, and are candidate biomarkers that may aid in the identification of the diagnostic boundaries of the two disorders.